Cooperation Between Actors In Food And Nutrition Policy For Stunting Prevention In Lamongan District - Muhammad Chusnul Khitam; Fahmi Anas (Jurnal Scientia, 2024)
As a step to support food policy in overcoming existing conditions regarding food and nutrition in Lamongan Regency, it is necessary to formulate a food policy which must be prepared in a structured and integrated action orientation. This research use desciptive qualitative approach. Research techniques were carried out using interviews, Forum Group Discussion, documentation studies and observations. The results of this research are that the Lamongan Regency Food and Nutrition Policy is a commitment to realizing community welfare through providing balanced, sustainable and inclusive food and nutrition. So collaboration is needed between various parties, including local governments, non-government organizations, the private sector and local communities. It is hoped that this joint effort can create synergy in the implementation of various programs covering aspects such as increasing food production, food diversification, nutrition education, strengthening community capacity and preventing stunting.